2022
DOI: 10.1097/dcr.0000000000002331
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging in Advanced Rectal Cancers: A Propensity-Matched Comparison Between Short-Course Radiotherapy Followed by Chemotherapy and Long-Course Chemoradiotherapy

Abstract: BACKGROUND: Short-course radiotherapy followed by chemotherapy has not been widely evaluated as an alternative to traditional long-course chemoradiotherapy in locally advanced rectal cancer. OBJECTIVE:This study compared the oncological and short-term outcomes between short-course radiotherapy + chemotherapy and long-course chemoradiotherapy in locally advanced rectal cancer.DESIGN: This is a retrospective propensity-matched study SETTINGS:The study was conducted in a colorectal department at a tertiary care o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The median duration between ostomy reversal and functional assessment was similar in both groups (24 months in LCRT vs 22 months in SCRT). The median Wexner scores were 6 (range, [4][5][6][7][8][9][10][11][12][13][14][15] in the LCRT group and 7 (range, [4][5][6][7][8][9][10][11][12][13][14] in the SCRT group (Table 2). No difference in the proportion of major incontinence was detected between the groups (8.1% in LCRT ) after SCRT (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median duration between ostomy reversal and functional assessment was similar in both groups (24 months in LCRT vs 22 months in SCRT). The median Wexner scores were 6 (range, [4][5][6][7][8][9][10][11][12][13][14][15] in the LCRT group and 7 (range, [4][5][6][7][8][9][10][11][12][13][14] in the SCRT group (Table 2). No difference in the proportion of major incontinence was detected between the groups (8.1% in LCRT ) after SCRT (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…4 Overall, downstaging seems to be superior with SCRT and chemotherapy based on pathological complete responses; however, the oncological superiority over LCRT is yet to be established. 3,5,6…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the benefit of SCRT for the reduction of local recurrence rates and improving long-term outcomes as compared to surgery alone [26] , [27] . Other studies showed that SCRT results in tumor downstaging and in some cases even in a clinical or pathological complete response after delayed surgery [9] , [12] , [28] , [29] . This has expanded the eligibility for organ-preserving treatment, aiming to maintain rectal function while effectively treating the cancer, enhancing a better QoL [30] , [31] .…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that surgical advances have been complemented by improvements in neoadjuvant treatments. Most recently, the use of total neoadjuvant therapy has become the standard of care in LARC [17][18][19][20][21], while early data on the use of immunotherapy has produced promising results [22]. However, the optimal management approach in LRRC remains unclear and varies substantially between regions [23,24].…”
Section: Discussionmentioning
confidence: 99%